Quality of Preterm Infants’ Night Sleep: and Online Community-Based Survey of Maternal Factors and Perceptions of Infants’ Nighttime Awakenings and Sleep Problems - Ali, Reem; Hall, Wendy; Warnock, Fay; Wong, Sabrina; Ratner, Pam (International Journal of Advanced Nursing Studies, 2014)
Background: Between one-quarter and one-third of infants aged six months to five years have sleeping problems. Infants' night sleep patterns, in particular problematic night waking with crying, are a common concern for parents. Many factors can influence the development of infants’ night sleep patterns and sleep problems, including parental interaction. Objectives: To examine the associations between premature infants’ nighttime awakening, mothers’ reports of sleep problem severity, and maternal factors, including mothers’ styles of attachment and behaviors used to settle their infants to sleep. Method: The cross sectional survey study used a web-based questionnaire to collect data from a community-based sample of 105 mothers of singleton premature infants aged 5-6 months (corrected age) across a number of English speaking countries. The main outcome measures were mothers’ perceptions of infants’ nighttime awakenings (frequency and duration) and presence of infant sleep problems. Results: Of the 55% of mothers who reported that their infants had sleep problems, 17% described the problem as serious. The majority of infants woke 2.1 times per night for an average of 45.7 minutes per night. Mothers’ style of attachment and personal history of sleep problems predicted the duration of the infants’ nighttime awakening, whereas maternal active physical comforting predicted the frequency of nighttime awakenings. Conclusions: The findings can guide healthcare providers to screen mothers for an anxious style of attachment, perceptions of infant sleep problems, and use of active physical comforting strategies for bedtime settling when assessing premature infants’ sleep problems. Keywords: Maternal Attachment, Nighttime Awakenings, Premature Infant, Settling Strategies, Sleep Problem